The Differences Levels of RANTES and PF4 Based on the Storage of Platelet Concentrate - Ni Made Rindra Hermawathi; Betty Agustina Tambunan; Arifoel Hajat (Indonesian Association of Clinical Pathologist and Medical laboratory, 2021)
Blood component transfusion is often used as the primary therapy as it is still considered safe. Platelet Concentrate (PC) transfusion plays a critical role in preventing bleeding in patients with severe thrombocytopenia. Allergic reactions are the most frequent transfusion reactions after PC administration. Regulated on Activation Normal T-Cell Expressed and Secreted (RANTES) and Platelet Factor 4 (PF4) cytokines released by platelets during PC storage are responsible for allergic reactions after transfusion. The purpose of this study was to analyze changes in RANTES and PF4 levels during PC storage. This study was an observational analytical research with a time series design carried out at the Clinical Pathology Laboratory and Blood Bank of the Dr. Soetomo Hospital, Surabaya, from June to July 2019. RANTES and PF4 levels in 27 bags derived from Platelet Rich Plasma (PRP) on storage for day 1, day 3, and day five were measured using the ELISA sandwich method. Subject same variant test or Friedman test was used for statistical analysis. The results showed no significant differences in RANTES and PF4 levels based on the storage duration of PCs on days 1, 3, and 5, with p=0.717, and p=0.614, respectively. There was no difference in the storage of PCs from day 1 to day five, and there was no effect on allergic reactions after PC transfusion.